2019
DOI: 10.1186/s12934-019-1200-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient simultaneous production of extracellular polyol esters of fatty acids and intracellular lipids from inulin by a deep-sea yeast Rhodotorula paludigena P4R5

Abstract: Background Polyol esters of fatty acids (PEFA) are a kind of promising biosurfactants and mainly secreted by Rhodotorula strains. In addition, some strains of Rhodotorula are reliable producers of microbial lipid. Therefore, it is feasible to establish a one step fermentation process for efficient simultaneous production of PEFA and microbial lipids by a suitable Rhodotorula strain. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…It is a member of glycoside hydrolase family 32 (GH32) with a size of 71.24 kDa and harbors conserved protein sequence motifs with the catalytic triad ( 192 D-316 D-366 E). Previous studies reported this enzyme also in other fungi identifying the well-known sequence signatures and catalytic triad of exo-inulinases [23][24][25]. In conclusion, our results suggest that the fungal mannitol pathway and exo-inulinase enzyme hold key roles for PEFA production in Rhodotorula strains.…”
Section: Biosynthetic Potential Of the Deep-sea R Mucilaginosa 50-3-supporting
confidence: 74%
See 4 more Smart Citations
“…It is a member of glycoside hydrolase family 32 (GH32) with a size of 71.24 kDa and harbors conserved protein sequence motifs with the catalytic triad ( 192 D-316 D-366 E). Previous studies reported this enzyme also in other fungi identifying the well-known sequence signatures and catalytic triad of exo-inulinases [23][24][25]. In conclusion, our results suggest that the fungal mannitol pathway and exo-inulinase enzyme hold key roles for PEFA production in Rhodotorula strains.…”
Section: Biosynthetic Potential Of the Deep-sea R Mucilaginosa 50-3-supporting
confidence: 74%
“…The knowledge on the PEFA biosynthetic pathway and its components is limited. A recent study suggested that an exo-inulinase enzyme holds key roles in the PEFA production via a mannitol biosynthesis pathway using the polysaccharide inulin as the carbon source [ 23 ]. Hence, we used the recently identified protein sequence of exo-inulinase enzyme from R. paludigena P4R5 [ 23 ] to detect enzymes in the marine R. mucilaginosa 50-3-19/20B genome aided by BLAST suite [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations